PREGABALIN VS. DULOXETINE FOR POSTOPERATIVE ANALGESIC REQUIREMENTS FOLLOWING LOWER LIMB ORTHOPAEDIC SURGERY: A RANDOMIZED STUDY. - Raj, Kritika; Tiwary, Praveen Kumar; Kumar, Mukesh; Suman, Saurabh; Lakra, Ladhu (Student’s Journal of Health Research Africa, 2024)
Background After lower limb procedures, acute postoperative pain must be managed well for patient recovery. Preemptive analgesics Pregabalin and Duloxetine, with different mechanisms, are promising. The study evaluates the effectiveness of Pregabalin versus Duloxetine in managing acute post-operative pain following lower limb orthopedic surgeries. Methods 120 individuals were included receiving spinal anaesthesia for elective lower limb procedures were included. Three groups of participants were created: Group P (pregabalin, n=40), Group D (duloxetine, n=40), and Group C (control, n= 40). The Visual Analogue Scale (VAS) was used to measure pain at different postoperative intervals. The Ramsay sedation scale was used to gauge the degree of sedation. Evaluations were also conducted on patient satisfaction, adverse effect frequency, and opioid intake. Version 16 of SPSS was used for statistical analysis. Results The three groups had similar mean ages, for Group C (34.80 ± 13.557), Group D (36.48 ± 15.262), and Group P (35.18 ± 13.756). The VAS scores indicated significantly lower pain levels in Group P at 2, 4, 6, and 12 hours postoperatively compared to Groups C and D (P < 0.001). Group P also showed significantly lower opioid consumption (130.88 ± 14.627 mcg/kg) compared to Groups C and D (P < 0.001). Sedation levels were higher in Group P at 2 and 4 hours postoperatively (P = 0.001). Side effects included sedation in Group P and post-operative nausea and vomiting in Group D. Conclusion Though it caused more drowsiness, pregabalin reduced immediate post-operative pain and opioid use after lower limb procedures better than Duloxetine. Duloxetine was beneficial but increased postoperative nausea and vomiting. Recommendations Pregabalin is suggested for immediate postoperative pain in lower limb procedures due to its superior pain relief and opioid-sparing benefits. However, its sedative qualities should be considered and used only in those who can take more sedation.